PENGARUH HARGA MINYAK, INFLASI, KEBIJAKAN DEVIDEN, LEVERAGE, DAN NILAI TUKAR RUPIAH, TERHADAP NILAI PERUSAHAAN (Studi Empiris Perusahaan yang Terdaftar Di LQ45 Periode 2012- 2016) - Roy Reksa Yusuf Birawa, 13.05.62.0023; Kartika, Andi (Students' Journal of Accounting and Banking, 2019)
The purpose of this study is to investigates the effects of inflation, dividend policy, leverage, rupiah exchange rate, and interest rate toward the company value in the company registered in LQ45 index. The sampling method uses purposive sampling with the research period from 2012 to 2016. The relationship or influence between variables is explained using the multiple regression analysis method. The results show that oil prices have a significant negative effect on firm value, inflation has no significant negative effect on firm value, dividend policy and exchange rate have a significant positive effect on firm value, leverage has a positive and insignificant effect on firm value. The last summary of this research is recommended as an input for the investors that 4 variables that investigated in this research do not affect the company value significantly. This research has restrictiveness, they are the period of collecting sample is relatively short; there are no considerations among variables, and the internal factors of Company presented in the financial report.